Pulmonary Toxicity After Total Body Irradiation – Critical Review of the Literature and Recommendations for Toxicity Reporting - Vogel, Jennifer; Hui, Susanta; Hua, Chia-Ho; Dusenbery, Kathryn; Rassiah, Premavarthy; Kalapurakal, John; Constine, Louis; Esiashvili, Natia (Frontiers in Oncology, 2021)
Introduction Total body irradiation is an effective conditioning regimen for allogeneic stem cell transplantation in pediatric and adult patients with high risk or relapsed/refractory leukemia. The most common adverse effect is pulmonary toxicity including idiopathic pneumonia syndrome (IPS). As centers adopt more advanced treatment planning techniques for TBI, total marrow irradiation (TMI), or total marrow and lymphoid irradiation (TMLI) there is a greater need to understand treatment-related risks for IPS for patients treated with conventional TBI. However, definitions of IPS as well as risk factors for IPS remain poorly characterized. In this study, we perform a critical review to further evaluate the literature describing pulmonary outcomes after TBI. Materials and Methods A search of publications from 1960-2020 was undertaken in PubMed, Embase, and Cochrane Library. Search terms included “total body irradiation”, “whole body radiation”, “radiation pneumonias”, “interstitial pneumonia”, and “bone marrow transplantation”. Demographic and treatment-related data was abstracted and evidence quality supporting risk factors for pulmonary toxicity was evaluated. Results Of an initial 119,686 publications, 118 met inclusion criteria. Forty-six (39%) studies included a definition for pulmonary toxicity. A grading scale was provided in 20 studies (17%). In 42% of studies the lungs were shielded to a set mean dose of 800cGy. Fourteen (12%) reported toxicity outcomes by patient age. Reported pulmonary toxicity ranged from 0-71% of patients treated with TBI, and IPS ranged from 1-60%. The most common risk factors for IPS were receipt of a TBI containing regimen, increasing dose rate, and lack of pulmonary shielding. Four studies found an increasing risk of pulmonary toxicity with increasing age. Conclusions Definitions of IPS as well as demographic and treatment-related risk factors remain poorly characterized in the literature. We recommend routine adoption of the diagnostic workup and the definition of IPS proposed by the American Thoracic Society. Additional study is required to determine differences in clinical and treatment-related risk between pediatric and adult patients. Further study using 3D treatment planning is warranted to enhance dosimetric precision and correlation of dose volume histograms with toxicities.